Arterial hypertension in patients with atrial fibrillation in Europe: A report from the EURObservational Research Programme pilot survey on atrial fibrillation. (1st March 2018) - Dan, G.A.; Badila, E.; Weiss, E.; Laroche, C.; Boriani, G.; Dan, A.; Tavazzi, L.; Maggioni, A.P.; Crijns, H.J.; Popescu, R.; Blommaert, D.; Streb, W.; et al.
Abstract: Background: Hypertension (HTN) is the most prevalent co-morbidity among atrial fibrillation (AF) patients; the relationship between the two is bidirectional, with an incremental effect on adverse outcomes. Purpose: To study clinical features, treatment patterns and 1 year outcomes amongst AF patients with HTN in the EURObservational Research Programme Atrial Fibrillation (EORP-AF) Pilot Registry, a prospective multi-national survey conducted by theEuropean Society of Cardiology in 9 European countries. Methods: Of 3119 enrolled AF patients, 2194 were diagnosed with HTN (AF-HTN) and 909 were normotensive (AF-NT) (16 patients had unknown HTN status). We compared baseline clinical features, management strategy and 1-year outcomes in terms of all-cause death, cardiovascular (CV) death, and any thrombosis-related event (TE: stroke, transient ischemic attack, acute coronary syndrome, coronary intervention, cardiac arrest, peripheral/pulmonary embolism) in AF-HTN vs AF-NT patients. Results: The AF-HTN patients had more prevalent CV risk factors and comorbidities (median CHA2DS2-VASc score (IQR) 4 (3, 5) in AF-HTN, versus 2 (1, 3) in AF-NT; p  < 0.01). Crude rate of all-cause death and any TE event was higher in AF-HTN (194 (11.2%) versus 60 (8.2%), p  = 0.02). Kaplan-Meier analysis curves for death by hypertensive status showed no significant differences between the subgroups (log rank test, p  = 0.22). On logistic regression analysis, HTN did not emerge as an independent risk factor for outcomes (OR 1.08, 95% CI 0.76–1.54). Conclusion: AF-HTN patients have a higher prevalence of comorbidities and this conferred a higher risk for a composite endpoint of all-cause death and thromboembolic events. In this cohort HTN did not independently predict all-cause mortality at 1-year.